Let us translate the given statement :
For every x,if x is a fish, then for every y, if y eats x then y is bear..
This is enforcing the condition that every animal that eats a fish is a bear.. So only option d matches..
option a:Every fish is eaten by some bear
$\forall x(F(x)\Rightarrow\exists y(B(y)\wedge E(y,x)))$
ie. for all x, if x is a fish, then there is a y such that y is a bear and y eats x.
option b:Bears eat only fish
$\forall x(B(x)\Rightarrow\forall y (E(x,y)->F(y))$
i.e for every x, if x is a bear,then for all y ,if x eats y, then y is a fish.
option c:Every bear eats fish
$\forall x(B(x)\Rightarrow\exists y (F(y)\wedge E(x,y))$
for all x, if x is a bear, then there is a y such that, y is a fish and x eats y.